A Case of Cervical Ectopic Pregnancy (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Cervical ectopic pregnancy is the implantation of a pregnancy in the endocervix1. Such pregnancy typically aborts within the first trimester, if it is implanted closer to the uterine cavity called cervico isthmic pregnancy it may continue longer2. Cervical pregnancy accounts for less than 1% of all ectopic pregnancies, with an estimated incidence of one in 2500 to one in 180003-5. Though the pregnancy in this area is uncommon but possibly life threatening condition due to risk of severe hemorrhage and may need hysterectomy. Early detection and conservative approach of treatment limit the morbidity and preserve fertility. A 26 years lady diagnosed as a case of cervical ectopic pregnancy and managed conservatively successfully with adjunctive techniques like cervical artery ligation and cervical temponade to control haemorrhage. The case is reported here for its relative rarity.Bangladesh J Obstet Gynaecol, 2012; Vol. 27(1) : 31-35